Esslen's politik des auswartigen handels - Taussig, F. W.; Esslen, Joseph Bergfried (Quarterly Journal of Economics, 1927)
Journal Article Esslen's Politik Des Auswärtigen Handels Get access F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 41, Issue 2, February 1927, Pages 338–344, https://doi.org/10.2307/1883505 Published: 01 February 1927